Implementasi Traditional Games Pantok Lele untuk Meningkatkan Literasi Spasial Skill Siswa pada Pelajaran IPS Terpadu - Rizkika Ramadani Subirto; Nurin Rochayati; Arif Arif; Mas’ad Mas’ad (Mataram University, 2026)
This study aims to improve students’ spatial literacy skills through the implementation of a games-based learning model using the traditional game Pantok Lele. This game is a cultural heritage of the Sasak ethnic group, rich in values of cooperation, sportsmanship, and spatial orientation. The research was conducted at MTs NW Penendem, East Lombok Regency, West Nusa Tenggara, involving 20 students of class VII-A as the research subjects. The method used was Classroom Action Research (CAR) referring to the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages conducted in two cycles. Data were collected through observation, tests, and questionnaires, and analyzed using descriptive qualitative and quantitative approaches. The results showed a significant improvement in students’ spatial thinking abilities, with the average pre-test score of 61.05 increasing to 75.45 in the first cycle and reaching 85.95 in the second cycle. The implementation of the Pantok Lele game proved effective in creating an active, collaborative, and enjoyable learning environment. In addition to enhancing spatial skills, this activity also fostered social, cultural, and cooperative values among students. Therefore, traditional game-based learning can be used as an innovative strategy to strengthen spatial literacy while preserving local culture.